Analysis of Factors Affecting the Stress Level and Self-Medication Practice in Primary Dysmenorrhea in Adolescents during COVID-19 Pandemic - Nurul Kusumawardani; Endang Darmawan; Jasmine Amira Hatisuci; Iftita Nuratika Ramadhanti; Rahma Sakti Oktavia; Very Ainun Fauziah; Trisna Styawaty; Ratih Nugraeni (Universitas Airlangga, 2022)
Background: During the novel coronavirus (COVID-19) pandemic, reports of adolescent pain and worsening of the menstrual cycle increased with increasing stress levels. Objective: Analysis of determinant factors that influence the ability to self-medication for menstrual pain, including socio-demography and medical history, to determine the effect of stress levels on the menstrual cycle of adolescent women during the COVID-19 pandemic. Methods: The method is descriptive observational, through a cross-sectional study on adolescent females in Indonesia was conducted in October-November 2020. Data collection through a simple survey method using a self-medication online questionnaire survey and the Kessler psychological distress scale (KPDS) by consecutive sampling technique. About 258 women agreed to participate in the study. The results are presented in the form of frequency and percentage (%), and the determinants are analyzed using Ï‡2-test and binary logistic regression models. Result: About 78.3% of respondents had stress during the pandemic COVID-19 with primary dysmenorrhea (70.2%), and 58.9% of respondents had low self-medication for managing primary dysmenorrhea. The predictors of self-medication understanding were the mother's education level and history of menstrual pain (p-value = 0.045; 0.005). In addition, respondents' stress levels during the COVID-19 pandemic affected their menstrual cycles (OR=5.110; 95% CI: 1.767–14.782, p-value=0.003). Conclusion: The role of pharmacists in the community and mothers as pioneers of family health is vital in increasing the understanding and implementation of the practice of self-medication for primary dysmenorrhea. This role needs to manage the stress of adolescent women. It can affect the reduction in the menstrual cycle, especially during the COVID-19 pandemic.